2020
DOI: 10.1124/jpet.120.000109
|View full text |Cite
|
Sign up to set email alerts
|

Semi-Mechanistic Pharmacokinetic Modeling of Lipid Core Nanocapsules: Understanding Quetiapine Plasma and Brain Disposition in a Neurodevelopmental Animal Model of Schizophrenia

Abstract: This study investigated plasma and brain disposition of quetiapine lipid core nanocapsules (QLNC) in naïve and schizophrenic (SCZ-like) rats and developed a semi-mechanistic model to describe changes in both compartments following administration of drug in solution (FQ) or nanoencapsulated. QLNC (1 mg/mL) presented 166 ± 39 nm, low polydispersity, and high encapsulation (93.0 ± 1.4%). Model building using experimental data from total and unbound plasma and unbound brain concentrations obtained by microdialysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The biggest limitation of this work is related to SCZ, which is a very complex disease and difficult to mimic in an animal model, although the animal model used presents face, predictive, and construct validity 27,28 . It is also important to point out that DA concentrations were investigated only in mPFC, which is not the brain region where the QTP effect is more pronounced, 29 although previous work from our group has demonstrated that QTP levels in the hippocampus and mPFC did not differ after FQ and QLNC administration 19 . From a translational point of view, the current contribution untangles drug effects into disease status, PK, and PD, allowing an in silico investigation integrating human PK and drug PD properties.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The biggest limitation of this work is related to SCZ, which is a very complex disease and difficult to mimic in an animal model, although the animal model used presents face, predictive, and construct validity 27,28 . It is also important to point out that DA concentrations were investigated only in mPFC, which is not the brain region where the QTP effect is more pronounced, 29 although previous work from our group has demonstrated that QTP levels in the hippocampus and mPFC did not differ after FQ and QLNC administration 19 . From a translational point of view, the current contribution untangles drug effects into disease status, PK, and PD, allowing an in silico investigation integrating human PK and drug PD properties.…”
Section: Discussionmentioning
confidence: 99%
“… 27 , 28 It is also important to point out that DA concentrations were investigated only in mPFC, which is not the brain region where the QTP effect is more pronounced, 29 although previous work from our group has demonstrated that QTP levels in the hippocampus and mPFC did not differ after FQ and QLNC administration. 19 From a translational point of view, the current contribution untangles drug effects into disease status, PK, and PD, allowing an in silico investigation integrating human PK and drug PD properties. Also, we highlight the importance in evaluating PK and PD in a disease animal model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation